Lichenoid papulovesicular eruption following measles. - Subramanian, S.; Phiske, M.; Kapoor, R.; Jerajani, H.R. (European Journal of Pediatric Dermatology, 2005)
According to Gianotti, Papulovesicular Acrolocated Syndrome (PAS) is characterized by multiple papules distributed symmetrically on face, neck, buttocks, and limbs and not associated with hepatitis B virus. This eruption is, on the other hand, associated with many viruses like EBV, Coxsackie, Echovirus etc.. Moreover, it may follow immunization with mumps, measles and rubella. We report a rare case of PAS-like eruption in a 8-year-old girl arisen 3 weeks after the clinical appearance of measles.